The effect of legal, norms and ethical values from Tawhidic paradigm on harmonious SME entrepreneurship and Malaysian society - Anor Salim, Farah Akmar; Mhd. Sarif, Suhaimi; Maidin, Ainul Jaria (2014)
The study explores the effect of legal, norms and ethical values from Tawhidic paradigm on achieving harmonious SME entrepreneurship and Malaysian society. Entrepreneurship setting comprises three main criteria, namely, legal, norms and ethical values. Observing legal requirement in various aspects related to business, entrepreneurship and society is essential to maintain entrepreneurial legitimacy. Apart from complying the law, entrepreneurship develops its own norms in terms of written (code of ethics) and tacit self regulation (words of mouth). Tawhidic paradigm manifests internal control based on Islamic and Imanic spirituality. The combination of external and internal control with Islamic and Imanic spirituality contributes to the harmonious relationship between the SME entrepreneurship and Malaysian society. The study obtains views through personal interview with selected Malaysian SME entrepreneurs in Klang Valley. The preliminary results show that the engagement into legal, norms and ethical values is still at premature stage as the SMEs are struggling to survive. However, the modular SME entrepreneurship under the guidance of various SME agencies in Malaysia such as FAMA, SME Corporation, TEKUN, and TERAJU, entrepreneurs are aligned harmoniously between the business and the society. The future study should use more rigorous and comprehensive instruments and to get more informants for study